Climate Change in Developing Countries - van Drunen, M. A.; Dorlands, C.; Lasage, R.; Ebooks Corporation (Wallingford : CABI, 2006)
This book presents an overview of the studies conducted by the Netherlands Climate Change Studies Assistance programme. The programme was set up in recognition of the need for developing countries, in particular, to face the challenges confronting all countries under the UN Framework Convention on Climate Change.
Contenido: 1.5.4 Adaptation assessment approaches in the NCCSAP2. Country Experiences and Highlights; 2.1 Introduction; 2.2 Bolivia; 2.2.1 Introduction; 2.2.2 Approach; 2.2.3 Results; 2.2.4 Experiences and lessons learned; 2.2.5 Follow-up research; 2.2.6 Policy implications; 2.2.7 Conclusions; 2.3 Colombia; 2.3.1 Introduction; 2.3.2 Approach; 2.3.3 Results of the Gulf of M
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: CAMBIOS CLIMATICOS